Physico-chemical properties of palm stearin, soybean oil and their binary blends / Nabilah Abdul Hadi - Abdul Hadi, Nabilah (2013)
The objective of this study was to determine the changes in physicochemical properties of palm stearin (PS) and soybean oil (SBO) blends at different mixing ratios in order to identify the suitable blend ratio of PS and SBO for certain food applications. Palm stearin was blended with SBO at different ratios of 70:30, 50:50 and 30:70 PS:SBO. The physicochemical properties of PS, SBO and PS:SBO binary blends were determined based on the major fatty acid composition, triacylglycerol profile, iodine value (IV), solid fat content (SFC), slip melting point (SMP) and hardness index (HI). Results indicated that the addition of SBO into PS caused the changes amount in fatty acid composition (FAC) of PS which cause decreased in the palmitic acid but increased in the linoleic acid. These results was supported with triacylglycerols (TAG) profile where the major TAG for PS which was 2-oleo-dipalmitin (POP) was decreased upon dilution with SBO, and increased the triunsaturated acid namely trilinolein (LLL). Blending PS and SBO resulted the IV increased significantly (p<0.05) with the increasing amount SBO thus decreased the SFC, SMP, and HI for all of the blends. Based on SFC, the blend 50:50 PS:SBO have a product stability and resistance to oiling out, with good melting point below body temperature which might be suitable for product such as margarine that must be melted in the mouth with minimum waxiness in order to have a good oral-melt